Effect of deposition rate and substrate microstructure on gas sensitivity of Te thin films - Olga Mocreac (Zaštita Materijala)
Tellurium thin films have been prepared using different rates (0.1 ÷ 30 nm/s) by physical deposition in vacuum on glassy, sintered alumina and electrochemically nanostructured Al2O3 substrates. The sensitivity to nitrogen dioxide of fabricated films was tested at room temperature. It is shown that the deposition rate strongly influences the microstructure of the films in question, as well as their gas sensing properties. The increasing of deposition rate results in transformation of microcrystalline structure of the film into an amorphous one. Simultaneously, both the gas - sensitivity and the response time decrease. The results are explained in terms of interaction between gas molecule and lone - pair electrons of tellurium atoms.